Ownership Elasticities of Durable Consumer Goods - Cramer, J. S. (Review of Economic Studies, 1958)
Journal Article Ownership Elasticities of Durable Consumer Goods Get access J. S. Cramer J. S. Cramer Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 25, Issue 2, February 1958, Pages 87–96, https://doi.org/10.2307/2296206 Published: 01 February 1958